Pre-existing sleep problems as a predictor of post-acute sequelae of COVID-19 - Schilling, Claudia; Nieters, Alexandra; Schredl, Michael; Peter, Raphael S.; Rothenbacher, Dietrich; Brockmann, Stefan O.; Göpel, Siri; Kindle, Gerhard; Merle, Uta; Steinacker, Jürgen M.; Kern, Winfried V. (Journal of sleep research, 2023)
Several months after COVID-19 many individuals still report persisting symptoms, the so-called ‘post-COVID-19 syndrome’. An immunological dysfunction is one of the main pathophysiological hypotheses. As sleep is central to the functioning of the immune system, we investigated whether self-reported pre-existing sleep disturbance might be an independent risk factor for the development of post-COVID-19 syndrome. A total of 11,710 participants of a cross-sectional survey (all tested positive for severe acute respiratory syndrome coronavirus-2) were classified into probable post-COVID-19 syndrome, an intermediate group, and unaffected participants at an average of 8.5 months after infection. The case definition was based on newly occurring symptoms of at least moderate severity and ≥20% reduction in health status and/or working capacity. Unadjusted and adjusted odds ratios were calculated to investigate the association between pre-existing sleep disturbances and subsequent development of post-COVID-19 syndrome while controlling for a variety of demographic, lifestyle, and health factors. Pre-existing sleep disturbances were found to be an independent predictor of subsequent probable post-COVID-19 syndrome (adjusted odds ratio 2.7, 95% confidence interval 2.27-3.24). Sleep disturbances as part of the post-COVID-19 syndrome were reported by more than half of the participants and appeared to be a new symptom and to occur independent of a mood disorder in most cases. Recognition of disturbed sleep as an important risk factor for post-COVID-19 syndrome should promote improved clinical management of sleep disorders in the context of COVID-19. Further, it may stimulate further research on the effect of improving sleep on the prognosis of COVID-19 long-term sequelae and other post-viral conditions.